Entrepreneurship - Hisrich, Robert D.; Peters, Michael P. (Boston, Mass. : Irwin/McGraw-Hill, 2000)
Business
Keywords: Entrepreneurship; New business enterprises; Business planning; Business enterprises-Finance; Success in business